Vue sur la technique de point de vue dans le ROUGE ET LE NOIR de Stendhal (Journal of the College of Languages (JCL), 2014)
It is axiomatical that the narrative prospective is profoundly significant to the writer who intends to commence his sketch of projected novel. It is the pillar of comprehensive absorbing as the writer should commit himself to circular his own concepts to the reader of his narrative characters. The dilemma of plot-perception is a twofold aspect; partly offers the question: what is the authors stand in regard to his characters? And: what is the aim of this theme? These correlative questions are inseparable since the reader who wishes to perceive the concept is governed by his intentions. When the author hides behind the third person this refers to the sort of implied and explicit relationships between the narrator and the reader out of one aspect and the narrator and receiver out of another. If the process of self-awareness is cloudy to some extent this reflects the key fact that the narrator is restricted to narrow horizons of the self; man as a dominator and being dominated, a doer and being done may not underestimate himself, so that in order not to lose the purity of objective prospective and to present narrative characters as required by them or in fact as they are in core; therefore establishing the third person is eminent by being prosperous therapy to maintain the objectivity away from individual impartiality.